Fallen skies - Gregory, Philippa (London : Harper Collins Publishers, 2006)
Lily Valance is determined to forget the horrors of World War I by throwing herself into the decadent pleasures of the 1920s and pursuing her career as a music hall singer. When she meets decorated veteran Captain Stephen Winters, she's immediately drawn to his wealth and status. And Stephen, burdened by his guilt over surviving the Flanders battlefields where so many soldiers perished, sees the possibility of forgetting his anguish in Lily, but his family does not approve. They marry, only to discover that his family's façade of respectability conceals a terrifying combination of repression, jealousy and violence. When Stephen's terrors merge dangerously close with reality, the truth of what took place in the mud and darkness brings him and all who love him to a terrible reckoning.
Keywords: World War, 1914-1918 -- Psychological aspects -- Fiction; Women singers -- Fiction; Great Britain -- History -- George V, 1910-1936 -- Fiction; Domestic fiction; Musical fiction; Historical fiction; War stories